Education as a Strategic Goal in the Croatian Non-Profit Sector after Communism and the War (European Journal of Mental Health, 2008)
In the past fifteen years considerable efforts have been made in Croatian society to increase the quality of leadership in both the non-profit as well as the profit sector. In the nonprofit sector education and training have been realised for leaders in non-governmental, faith and charity organisations as well as in public, educational and social care institutions. As well as many informal additional forms of education (improvement, advanced training, work on oneself) much education has been provided by non-profit organisations, for example the Open Society. Croatia defines education as a strategic goal. Inside the educational system research and experience show the importance of management and leadership in educational institutions as well as in the social care system. We are of the opinion that lack of knowledge and skills adds up to poverty. It makes sense that increasing the quality of leadership in the educational system should be one of the first strategic points for development. An improvement in the quality of management is dependent on the efficiency and the effectiveness of the educational system. Caritas Croatia, through a new mission in cooperation and partnership with Caritas Germany, Deutscher Caritasverband and the German government, has established a formal educational system for leadership in non-profit organisations through postgraduate study: Management for Nonprofit Organisations and Social Advocacy. Education is a part of the non-profit sector described in diagrams. Education basically rests on non-profit governmental institutions (institutions for education, schools), but educational suppliers are both profit and non-profit organisations. Research was conducted in order to find the answers to omit open questions about leaders’ educational needs and the key of quality in the educational system as well as in the whole non-profit sector.